PENGARUH KUALITAS LAYANAN, IMAGE DAN VARIASI PRODUK TERHADAP KEPUASAN PELANGGAN KOPERASI KAREB BOJONEGORO - Adi Rizki Suwito (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
This study aims to determine and analyze the impact of service quality, image and product variation both simultaneously and partially to customer satisfaction Kareb Cooperative Bojonegoro District. And to know and analyze among variables of service quality, image and product variation which have dominant influence on customer satisfaction of Kareb Cooperative of Bojonegoro Regency. The population in this study are all customers of Cooperative Kareb Bojonegoro which recorded as many as 409 people. The number of samples in this research is 70 people. Data analysis techniques used in this study is a simple linear regression Calculator using SPSS program. The results of data analysis show that the quality of service, image and product variation simultaneously have significant effect on customer satisfaction of cooperative Kareb Bojonegoro. Image and product variation partially significant effect on customer satisfaction Kareb Bojonegoro cooperative. While the quality of service has no significant effect on customer satisfaction. Among the quality of service, image and product variation that has a dominant influence on customer satisfaction Kareb Cooperative of Bojonegoro Regency is a variety of products.